THE INFLUENCE OF DIET ON IRON ABSORPTION : III. COMPARATIVE STUDIES WITH RATS, MICE, GUINEA PIGS, AND CHICKENS - Hegsted, D. Mark (The Rockefeller University Press, 1952)
The response of rats, chicks, mice, and guinea pigs to two diets containing various amounts of iron has been compared. With diets composed chiefly of corn grits animals of all these species absorb and store considerably more iron than those with normal diets of the same iron content. If sufficient iron is added to a normal diet, all species will absorb large amounts of iron. However, there appear to be great species differences in the level of iron which must be fed to cause the increase in absorption. Chicks and mice appear to have less effective control over iron absorption on high iron diets. Attention is called to large individual differences in ability to control iron absorption under the conditions of these experiments.